Continuance intention to use mobile learning for second language acquisition based on the technology acceptance model and self-determination theory - He, Limin; Li, Chunming (Frontiers in Psychology, 2023)
This study examines the factors that predict Chinese students’ continuance intention to use mobile learning for second language acquisition based on the technology acceptance model and self-determination theory. 170 undergraduates have participated in the survey and the structural equation modeling is conducted to assess the validity of the integrated model and hypotheses. The findings show that instructor support can significantly predict autonomy, competence and relatedness. Autonomy and competence are positively related to perceived ease of use and continuance intention to use mobile learning for English acquisition. Relatedness significantly correlates with perceived ease of use but is not directly related to learners’ continuance intention. The relationship between perceived ease of use and continuance intention to adopt mobile learning is positive and significant. In addition, the results show that instructor support, autonomy, relatedness, competence and perceived ease of use can predict Chinese students’ continuance intention to use m-learning for second language acquisition, with 70.5% of the total variance in continuance intention being explained by these five variables. These results thus empirically support the integrated model, which can be used as a theoretical framework in future studies on mobile learning in higher education contexts. Moreover, the results of this study have a number of practical implications for universities and instructors.